Histone deacetylation inhibitors affect in vitro oocyte maturation and somatic cell nuclear transfer in pigs - Phitchanika Pankammoon; Chaimongkol Potiruean; Prakon Boontawee; Prapas Patchanee; Anucha Sathanawongs (Veterinary Integrative Sciences)
Histone deacetylase inhibitors (HDACi), such as Trichostatin A (TSA) and Valproic acid (VPA), are known treatment strategies to improve somatic cell nuclear transfer (SCNT) efficiency in various species, including porcine. However, their supportive roles in oocyte maturation and preimplantation embryonic development come with a prolonged meiotic division during in vitro maturation. This study examined the effects of TSA, VPA, and combined TSA and VPA treatments on porcine cumulus-oocyte complexes (COCs), as well as on parthenogenetic activation (PA)- and SCNT-derived embryos. Nuclear maturation of porcine oocytes in vitro was assessed through aceto-orcein staining, while the developmental rates of PA- and SCNT-derived embryos were also observed. Results revealed that TSA treatment significantly inhibited nuclear maturation in porcine oocytes, whereas VPA and TSA+VPA treatments did not differ significantly from the control. There were also no notable differences in blastocyst rates among PA-derived embryos. However, VPA treatment led to a higher blastocyst rate in porcine SCNT embryos. The combination of TSA and VPA appeared to have a synergistic effect on embryo development, with VPA supporting TSA’s effects. Overall, VPA treatment resulted in fewer inhibitory effects on oocyte maturation and improved embryo development more effectively than TSA. These findings contribute to our present understanding of the role of histone deacetylation in porcine oocyte and SCNT-derived embryo development during in vitro production.